Derivative free multilevel optimization - Karasozen, B (TWMS journal of applied and engineering mathematics, 2015)
Optimization problems with different levels arise by discretization of ordinary and partial differential equations. We present a trust-region based derivative-free multilevel optimization algorithm. The performance of the algorithm is shown on a shape optimization problem and global convergence to the first order critical point is proved. Keywords: Derivative-free optimization; multilevel optimization; shape optimization; trust-region methods. AMS Subject Classification: 90C30, 65K05, 90C26, 90C06, 90C56 ; 65D05.